Indeksi osetljivosti na hormone štitne žlezde i hs-CRP kao biohemijski prediktori sazrevanja arteriovenske fistule kod dijabetičke nefropatije: Thyroid Sensitivity and hs-CRP in AVF Maturation - Li, Dan; Zhao, Bing; Zou, Lihong (Journal of Medical Biochemistry, 2025)
Background: Autogenous arteriovenous fistula (AVF) maturation is essential for successful hemodialysis in patients with diabetic nephropathy (DN). However, its outcome is often unpredictable. Thyroid hormone sensitivity indices and biochemical markers may provide valuable laboratory predictors for AVF maturation.Methods: A total of 102 DN patients undergoing AVF surgery were retrospectively analyzed and classified into mature and immature AVF groups. Laboratory data, including thyroid hormone sensitivity indices [free triiodothyronine (FT3), free thyroxine (FT4), thyroid-stimulating hormone (TSH), FT3/FT4 ratio, thyroid-stimulating hormone index (TSHI), thyroxine resistance index (TT4RI), thyroid feedback quantile index (TFQI), and parameterized TFQI (PFTQI)], as well as biochemical markers such as high-sensitivity C-reactive protein (hs-CRP), albumin, total cholesterol, triglycerides, and LDL-C, were compared. Doppler ultrasonography was used as supportive assessment. Logistic regression identified independent predictors of AVF maturation.Results: Patients in the AVF Maturity Group exhibited significantly lower FT3, TSH, FT3/FT4 ratio, TSHI, TFQI, and PFTQI levels, along with reduced hs-CRP values (all P < 0.05). Multivariate logistic regression revealed that higher FT4, TFQI, and PFTQI, lower hs-CRP, larger cephalic vein diameter, and younger age were independently associated with successful AVF maturation.Conclusion: Thyroid hormone sensitivity indices and hs-CRP serve as important biochemical predictors of AVF maturation in DN patients. These laboratory parameters may assist in risk stratification and clinical decision-making, providing a biochemical perspective for optimizing dialysis access outcomes.